Keterlibatan Gen-Z pada Merek m-BCA: Analisis Pengaruh Pengalaman Merek terhadap Kepuasan dan Loyalitas Merek - Syahwiati, Aisya Sukma; Sihotang, Ellen Theresia (Nur Science Institute, 2024)
Gen-Z has intensive access to internet technology, which has made it the market share of financial digital services, including banks. The Top Brand Index (TBI) 2024 survey states that m-BCA is included in the first top brand category. Referring to the survey results, this study aims to measure the engagement of gen-Z in the m-BCA brand on brand experience and its influence on the satisfaction and loyalty of the m-BCA brand. The sample used was 200 gen-Z who live in Surabaya and Sidoarjo with judgment sampling technique. The data analysis method used is SEM-PLS. Gen-Z engagement in the m-BCa brand positively and significantly affects the brand experience. The positive experience of Gen-Z has a significant effect on brand satisfaction and loyalty. Gen-Z satisfaction with the m-BCA brand has a positive and significant effect on brand loyalty. The generation's engagement significantly influences Gen-Z's experience with the m-BCa brand and its loyalty.